Atmanirbhar Bharat Abhiyan and National Education Policy – 2020: Opportunities and Challenges for India’s Sustainable Development (Indian Journal of Social Science and Literature (IJSSL), 2024)
The Atmanirbhar Bharat Abhiyan and the National Education Policy (NEP) are two key initiatives launched by the Government of India. Atmanirbhar Bharat aims at promoting economic self-reliance. NEP encourages innovation, entrepreneurship and self sufficiency in various areas. This research paper examines the inter-linkages between the Atmanirbhar Bharat Abhiyan and the NEP and their potential impact on the Indian economy and education system. The paper also identifies the challenges and opportunities associated with the implementation of these initiatives and propose policy recommendations to ensure their effective and sustainable implementation. The paper argues that the successful implementation of these initiatives requires a concerted effort and collaboration between various stakeholders and emphasizes the need for a holistic and collaborative approach to promote sustainable development in India.